Dataset for: Of Imagined and Potential Futures: Speculative Fiction in Southern Africa (2008-2018) - Woods, Joanna Polly (Stockholm University, 2023)
This research project explores the rhetorical function of contemporary Anglophone speculative fiction in southern Africa. Focusing on short fiction produced between 2008 and 2018, the project delineates this literary production both theoretically and historically. It is the “difference” of contemporary African speculative fiction that needs attention, the thesis argues, and through such difference we might evaluate how this literature manifests as a prominent, collective call to de-colonise dominant ways of seeing.
Moreover, the contemporary speculative fiction scene in the southern region of the continent is not well represented in scholarship. To date, much more work has been done on, for example, speculative fiction in Nigeria, or indeed in South Africa. Similarly, far more studies exist on the novel form. And yet, it is a contention of this project that short sf is far more abundant in Africa today. The project therefore addresses a number of important gaps by providing perspective on short speculative fiction in Malawi, Zimbabwe, and South Africa. It also draws attention to various questions that will need further study in the field of Afrofuturism and Africanfuturism.
The methodological choice to view this literature within a rhetorical framework complicates the duality of culture and text characteristic of cultural studies and focuses instead on how relationships among texts, writers, publishing agents and readers function. This is especially relevant in an African literary studies context because such approach works to bypass practices of silencing and the appropriation of certain perspectives, reorients agency, and redirects the conversation to focus on interactions between literary actors more closely. Since little attention has been paid to African literary narratives from a rhetorical angle, even less to African speculative texts, an effort is made to fill this gap using pragmatic frames (Bitzer 1968), rhetorical narrative (Phelan 2007), and the “literary field” (Bourdieu 1993). In addition, the project draws insights from the social sciences to combine quantitative and qualitative methods of investigation.
The thesis consists of an introduction and three main chapters: “Mapping the Field”, “Ways of Seeing – Temporalities”, and “Ways of Seeing – Spatialities”. It also includes an Excel spreadsheet, in which much mapping of the scene occurs. Along with notes on authorship and production, the spreadsheet contains documentation of keywords noted while reading the sf short stories. Three keywords made themselves most manifest: time, space and ways of seeing, and thereafter helped to structure the latter chapters of the research project. The findings in the spreadsheet and interview material particularly inform Chapter One, which illuminates the emerging field of speculative fiction in the southern region of Africa by mapping the scene of production (2008-2018). Chapter Two investigates the rhetorical function of time and temporalities as nodes of interest in five speculative fiction texts. And, finally, the third chapter, explores to what effect space and spatialities are employed by sf writers in another five short stories.

The files contain interviewees speaking about short stories and speculative fiction production in southern Africa.
The dataset files comprise both audio-visual Zoom recordings (mp4, 9 files) [size ranges between 49 MB and 794.5 MB], and transcriptions of those recordings in MS Word documents (docx, 10 files) [document size ranges between 22 KB and 38 KB].
For most audio-visual files there is a corresponding MS document (i.e. transcript of the audio). But, there is one MS Word file without corresponding audio-visual file.
Mp4 software is needed to listen to / watch the audio-visual Zoom files; e.g. the files will open with Quick Time Player.

Detta projekt undersöker den retoriska funktionen av samtida engelskspråkig "speculative fiction" från södra Afrika. Den fokuserar på kort fiktion skriven mellan 2008 och 2018 och beskriver denna litterära produktion både ur ett teoretiskt och ett historiskt perspektiv. Avhandlingen argumenterar för att det är "skillnaden", det som särskiljer samtida afrikansk "speculative fiction", som kräver vår uppmärksamhet. Genom denna skillnad uppmanar fiktionen också till en tydlig, gemensam avkolonisering av dominerande sätt att se. ...

Filerna innehåller audio-video inspelningar (.mp4 , 9 filer) och transkriptioner (.docx, 10 filer) från intervjuer, där intervjupersonerna talar om produktionen av noveller och "speculative fiction" i södra Afrika. Alla audio-videofilerna har en transkriptionsfil, men det finns en transkription av en intervju som saknar motsvarande audio-video inspelning. Audio-videofilerna (.mp4) kan öppnas med t.ex. Quick Time Player eller andra videospelare.
Data för: Fantastisk litteratur från södra Afrika (2008-2018)
Keywords: Literature; litteratur; Languages and Literature; Språk och litteratur; General Literary studies; Litteraturvetenskap; Studies of Specific Literatures; Litteraturstudier